A new interpretation of the deep-part of Senegal-Mauritanian Basin in the Diourbel-Thies area by integrating seismic, magnetic, gravimetric and borehole data: Implication for petroleum exploration. (September 2016) - Ndiaye, Matar; Ngom, Papa Malick; Gorin, Georges; Villeneuve, Michel; Sartori, Mario; Medou, Joseph
Abstract: The Diourbel-Thies area is located in the centre of the onshore part of the Senegal-Mauritanian Basin (SMB). The new interpretation of old petroleum data (2-D seismic lines and drilling data of three oil wells) in the deeppart of this poorly evaluated zone, integrating gravimetric and magnetic data, has allowed the distinction of the Hercynian ante-rift phase (U1) which is distinguished from the syn-rift phase (U2) probably of Permo-Triassic to Middle Jurassic age. The syn-rift phase resulted in a series of compartments or grabens infilling aligned in a North-South direction. Tholeiitic volcanism of the Central Atlantic Magmatic Province (CAMP) is present in the syn-rift phase of the Diourbel-Thies area. The syn-rift deposits and associated volcanics allow us to surmise that the Diourbel basin represents a deeper rift basin. In comparison with other Central Atlantic Margins (CAM), the Diourbel rift basin could be one of the numerous rift basins that formed during the Permo-Triassic age. From a petroleum exploration perspective, the existence of the Diourbel rift basin is attractive because of the presence of structures that are excellent for deep gas exploration. Highlights: New interpretation of the deeper Senegal-Mauritanian basin. The Diourbel rift basin has been highlighted in the Senegal-Mauritania basin. Diourbel rift basin belongs to the Central Atlantic Margin. The tholeiitic volcanism has been highlighted in the Diourbel basin. Comparison with other Central Atlantic rift basins.